Optimizing Biotogrow Liquid Fertilizer Concentration and Application Frequency for Lettuce Cultivation Under Tropical Cambisol Conditions - Nendissa, Jeanne Ivonne; Wahditiya, Andi Adriani; Amba, Martha (Agro Bali : Agricultural Journal, 2025)
This greenhouse study investigated the impact of Biotogrow liquid organic fertilizer concentration and application frequency on lettuce (Lactuca sativa L.) growth and yield at Telaga Kodok from May to August 2024. The purpose of the research is to determine the effect of Biotogrow Liquid Fertiliser concentration and fertilisation interval, as well as the interaction between the two, on the growth and production of lettuce (Lactuca sativa L.). Using a factorial Randomized Complete Block Design with three replications, researchers tested four Biotogrow concentrations (0, 2, 5, and 8 ml L⁻¹) and four fertilization intervals (0, 4, 7, and 10 days). Growth parameters, including plant height, leaf number, leaf area, fresh weights, shoot-to-root ratio, and harvest index, were measured at 14, 21, 28, and 35 days after planting. ANOVA and Duncan's Multiple Range Test (α = 0.05) revealed significant findings. Biotogrow concentration substantially influenced plant height at 21, 28, and 35 DAP (P < 0.01), leaf number throughout all observation periods (P < 0.05 at 14 DAP; P < 0.01 thereafter), plus shoot and root fresh weight, leaf area, and harvest index (P < 0.01). Fertilization intervals significantly affected all parameters except the shoot-to-root ratio (P < 0.01). Importantly, concentration-interval interactions showed highly significant effects on leaf number at 35 DAP, shoot fresh weight, and leaf area (P < 0.01), with significant impacts on plant height at 28 and 35 DAP, leaf number at 28 DAP, and root fresh weight (P < 0.05). These results demonstrate that optimizing both Biotogrow concentration and application timing can significantly enhance lettuce productivity under greenhouse conditions.